Sixteen years of eHealth experiences in Iran: a qualitative content analysis of national policies - Seyyed Meysam Mousavi; Amirhossein Takian; Mahmood Tara (BMC, 2021)
Abstract Introduction As a building block of all health systems and a multi-sectoral domain, eHealth has a critical role to accelerate the achievement of sustainable development goals (SDGs), particularly universal health coverage (UHC). Our objective was to provide a better understanding of the recent experiences on eHealth policy, particularly in framing process of the policies and strategies, in an attempt to develop evidence-based recommendations that can inform future eHealth policy formulation, implementation, and development in Iran. Methods We undertook an exploratory, descriptive, comparative, retrospective and longitudinal analysis of eHealth policies by using content analysis of upstream and other key national policy documents, guided by criteria for reporting qualitative research (COREQ). A systematic and purposive search was conducted to identify publicly-accessible documents related to eHealth policies in Iran, followed by in-depth, semi-structured, open-ended interviews with purposefully identified national key informants in the field of eHealth. MAXQDA® 12 was used to assist with qualitative data analysis. Findings We retrieved and included 13 national policy documents demonstrating 16 years experiences of recorded eHealth policy in Iran, from 2004-2020. Our analysis revealed seven main categories as challenges of eHealth policies in Iran: (1) lack of comprehensive and big picture of all eHealth components; (2) lack of long-term and strategic plans on eHealth; (3) poor consistency among national policy documents; (4) unrealistic and non-operational timing of policy documents; (5) inappropriate identification and lack of involvement of key actors in development and implementation of eHealth policies; (6) low priority of eHealth in the national health system, and (7) unconventional focus and attention to Electronic Health Record (EHR). Conclusion The findings reveal almost two decades history of eHealth initiatives at the national and upstream policy level in Iran, with noticeable gaps between desired policies and achieved expectations. The inclusion of eHealth solutions in the policy documents has been controversial and challenging. eHealth seems to have not been meaningfully established in the minds and views of policy makers and senior manager, which might have led to the development of incomplete and contradictory policies. The health system in Iran needs, we advocate, the design of an evidence-informed eHealth roadmap, as well as continuous, systematic, and reasonably time-bounded strategic plans to establish eHealth as the building block of health system along the pathway towards sustainable health development.